Use of safinamide for treatment of Parkinson disease: real-world data from Spain - María Isabel Morales Casado; Nuria López Ariztegui (Drugs in Context, 2025)
Safinamide is a monoamine oxidase B inhibitor that was approved in Europe in February 2015 to complement a stable dose of levodopa in monotherapy or in combination with other antiparkinsonian agents in adults affected by mid-stage or advanced Parkinson disease (PD) with fluctuations. It is characterized by a dual mechanism of action (dopaminergic and non-dopaminergic), thus enabling an innovative approach in the management of motor and non-motor symptoms. The safety and efficacy profile of safinamide was previously shown in placebo- controlled randomized clinical trials, which demonstrated that ON time could be increased without the onset of dyskinesia and that OFF time could be decreased, with an improvement in PD. However, the strict inclusion and exclusion criteria in these studies meant that not all patients seen in daily clinical practice were represented, hence the importance of observational studies that evaluate the drug in these situations. The objective of the present article was to collect and review reports from Spanish authors presented at national and international conferences on the use of safinamide in patients with PD. We reviewed a total of 36 reports covering around 2000 patients with PD. The reports confirm the safety and efficacy results obtained in clinical trials, showing a significant improvement in motor and non-motor fluctuations and enabling the dose of levodopa to be reduced, thus decreasing the likelihood of motor complications.